Humanizing Technology: The Role of Quranic Etiquettes and Shariah Ethics in AI-Based Learning Environments - Ayesha Siddika (Faculty of Syariah and Law, USIM, 2026)
Artificial intelligence brings innovation to every sector of life. However, concerns are growing alongside AI’s popularity that moral literacy may decline as a result of the rapid expansion and over-dependency of technology. This research is designed to rethink the use of technology and to investigate a conceptual framework for humanizing AI through the incorporation of etiquettes mentioned in the Quran and Shariah-based moral principles. In addition, the research aims to suggest pedagogical strategies that promote transparency, accountability, and moral responsibility in the context of AI-assisted education. To meet the objectives, this paper employed a convergent parallel mixed-method design to collect information from people with relevant expertise. Most respondents emphasized the humane aspects of knowledge over machine learning. The findings also recommend redesigning and modifying AI algorithms to incorporate etiquette from the Quran and Shariah-based principles. The current study presents the emphasis of etiquettes mentioned in the Quran and Islamic principles to administrate AI-based education.